Simulation and genetic optimization of control systems by LabVIEW programming - Zherebko, V.A.; Pisarenko, O.A.; Drabynko, V.P. (PROBLEMS IN PROGRAMMING, 2018)
The procedures for the engineering, synthesis, simulation and targeted implementation of algorithms for solving optimization problems in hierarchical automated control systems require complex objects using a variety of mathematical and software and hardware for research and engineering work. In this article the unification of mathematical and algorithmic support in the form of a unified concept of solving optimal control is proposed. We propose to use LabVIEW software and CompactRIO industrial controller as the unification of software and hardware implementation of mathematical-algorithmic developments, on which developed software tools to solve optimization problems using genetic algorithm.Problems in programming 2018; 2-3: 288-295